2008
DOI: 10.1002/hbm.20544
|View full text |Cite
|
Sign up to set email alerts
|

Mapping a multidimensional emotion in response to television commercials

Abstract: Unlike previous emotional studies using functional neuroimaging that have focused on either locating discrete emotions in the brain or linking emotional response to an external behavior, this study investigated brain regions in order to validate a three-dimensional construct--namely pleasure, arousal, and dominance (PAD) of emotion induced by marketing communication. Emotional responses to five television commercials were measured with Advertisement Self-Assessment Manikins (AdSAM) for PAD and with functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 29 publications
0
36
0
3
Order By: Relevance
“…Prior studies have revealed that consumers' emotional responses play a significant role for advertising effectiveness and attitude changes (Burke and Edell 1989;Holbrook and Batra 1987;Morris 1995;Morris, Woo, and Cho 2003;Morris et al 2009). The considerable amount of research has indicated that emotional response, or consumers' feelings toward ads, are one of the key factors contributing to brand attitude and behavioral intentions (Burke and Edell 1989;Holbrook and Batra 1987;Morris et al 2002;Stayman and Batra 1991).…”
Section: Emotional Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have revealed that consumers' emotional responses play a significant role for advertising effectiveness and attitude changes (Burke and Edell 1989;Holbrook and Batra 1987;Morris 1995;Morris, Woo, and Cho 2003;Morris et al 2009). The considerable amount of research has indicated that emotional response, or consumers' feelings toward ads, are one of the key factors contributing to brand attitude and behavioral intentions (Burke and Edell 1989;Holbrook and Batra 1987;Morris et al 2002;Stayman and Batra 1991).…”
Section: Emotional Responsementioning
confidence: 99%
“…The combination of three independent dimensions (AEE) measures the full spectrum of human emotions. The theory has been used extensively in the context of advertising and consumer research (Christ 1985;Christ and Biggers 1984;Morris, Woo, and Cho 2003;Morris et al 2009). This study adopted the AEE theory for measuring viewers' emotional response to the nostalgic content.…”
Section: Emotional Responsementioning
confidence: 99%
“…In these last years we assisted to an increased interest in the use of brain imaging techniques, based on hemodynamic or electromagnetic recordings, for the analysis of brain responses to the commercial advertisements or for the investigation of the purchasing attitudes of the subjects Knutson et al 2007;Astolfi et al 2008a; Morris et al 2009). The interest is justified by the possibility to correlate the particular observed brain activations with the characteristics of the proposed commercial stimuli, in order to derive conclusions about the adequacy of such ad stimuli to be interesting, or emotionally engaging, for the subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of differential activation in the SS region supports the conclusion that there is not simply a generalized increase in activity with LP stimuli across all brain regions, but rather that the differences have regional specificity. Morris et al (2009) examined brain activation while subjects watched TV advertisements during FMRI scanning and then rated ads along dimensional constructs of "pleasure" and "arousal." They found that bilateral activations in the inferior frontal and middle temporal gyri were associated with differences along the pleasure dimension, whereas the arousal dimension influenced activation in right superior temporal and right middle frontal gyri.…”
Section: Discussionmentioning
confidence: 99%